Effects of ligand substituents on the single-molecule magnetic behavior of quinonoid-bridged dicobalt compounds. Issue 20 (6th May 2020) - Zhu, Xiao-Quan; Cao, Wen-Hai; Su, Shao-Dong; Wu, Xin-Tao; Sheng, Tian-Lu
Abstract : The SMM behavior weakens until its disappearance with the substituent changing from Br, H to OMe in the quinonoid-bridged dicobalt compounds [(N4 Co)2 LX](ClO4 )2, (X = H, Cl, Br, and OMe). Abstract : A series of quinonoid-bridged dicobalt compounds [(N4 Co)2 LX](ClO4 )2 (1–4 ) (X = H, Cl, Br and OMe; N4 = 1, 4, 7, 10-tetrabenzyl-1, 4, 7, 10-tetraazacyclododecane) are synthesized and well characterized. Single crystal X-ray diffraction analyses reveal that the coordination geometry of one side Co in compounds 1–4 changes from a triangular prism to distorted octahedron with a change in the bridged-ligand substituent. Magnetic measurements show that compounds 1 and 3 exhibit single-molecule magnetic behavior. Magneto-structural analyses indicate that the difference in the relaxation barrier U between the four compounds results from the different orientations of the anisotropy axes of the two Co centers in the molecule.